MANAJEMEN PEMBINAAN PRESTASI BULUTANGKIS PB. PENDOWO KOTA SEMARANG - Hamzah Kholisunnia Murofiq; Pandu Kresnapati; Osa Maliki (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2025)
This research is motivated by the results of observations regarding the management of achievement development in the PB club. Pendowo Semarang. The problem studied is the lack of championship contributions at the national level. The aim of this research is to find out how to manage good performance development in badminton at the PB Club. Pendowo Semarang 2024. This research method uses a qualitative descriptive approach and carries out observations, interviews and documentation as data collection methods. Chief administrators, coaches and athletes are research subjects. The research results show that planning, organizing, implementing achievement coaching, and monitoring processes in PB. Pendowo Semarang has been implemented well. This involves the process of selecting athlete members and coaches, managing funding, organizational structure, documentation of achievements, training programs, facilities and infrastructure, as well as supervision from managers, coaches and parents of athletes.